Photocatalytic ability of visible-light-responsive hybrid ZrO2 particles. Issue 9 (13th April 2023) - Zarubica, Aleksandra; Sredojević, Dušan; Ljupković, Radomir; Randjelović, Marjan; Murafa, Natalija; Stoiljković, Milovan; Lazić, Vesna; Nedeljković, Jovan M.
Abstract : The interfacial charge transfer (ICT) complex formation between zirconium dioxide (ZrO2 ), the material absorbing below 250 nm, and 5-aminosalicylic acid (5-ASA) leads to the formation of visible-light-absorbing inorganic–organic hybrids. Abstract : The interfacial charge transfer (ICT) complex formation between zirconium dioxide (ZrO2 ), the material absorbing below 250 nm, and 5-aminosalicylic acid (5-ASA) leads to the formation of visible-light-absorbing inorganic–organic hybrids. The free amino groups, present on the hybrid's surface after the ICT complex formation, were used to reduce silver ions and link silver particles to ZrO2 . The prepared samples were characterized by using transmission electron microscopy, X-ray diffraction analysis, and nitrogen adsorption–desorption isotherms. Density functional theory (DFT) calculations using a cluster model are applied to explain optical changes in hybrids, i.e., absorption redshift induced by the ICT complex formation. Decolorization of an organic dye crystal violet (CV), under ultraviolet-C or visible light, was used to compare the photocatalytic ability of the prepared samples. The ICT complex formation transformed ZrO2 into a hybrid material able to induce photocatalytic reactions under exclusive visible light excitation.